PEMIDANAAN TERHADAP PELAKU TINDAK PIDANA PERZINAHAN (STUDI PUTUSAN PENGADILAN NEGERI STABAT NO : 221/PID .B/2014/PN.STB DAN PUTUSAN PENGADILAN NEGERI SIDIKALANG NO: 116/PID.B/2013/PN.SDK) - Syawal Saputra Siregar; Muhammad Hamdan; Mohammad Ekaputra; Utari Maharany Barus (USU LAW JOURNAL, 2017)
ABSTRACT The setting is the crime of adultery against unmarried couples will not only accommodate the religious law or customary law which has prohibited such actions but can prevent the spread of other criminal offenses such as abortion, child neglect or disposal of the child of a relationship outside of marriage and so forth caused by acts criminal adultery. That is, if the formulation of legislation in its entirety has been set for penal deterrence has been fulfilled, then only a non penal policy formulation. Related to the above description there are two (2) court decision that will be examined in this thesis, the Stabat District Court Decision No: 221/Pid.B/2014/PN.Stb and Sidikalang District Court Decision No: 116/Pid.B/2013/PN.SDK. It brings necessary to study the factors that lead to fornication punishable. Comparison of the crime of adultery is regulated in the Code of Penal (Penal Code) and Islamic law. Application of the criminal law against adultery by Stabat District Court Decision No: 221/Pid.B/2014/PN.Stb And Sidikalang District Court Decision No: 116/Pid.B/2013/PN.SDK. Keywords: Comparison, Crime and Adultery